Archaeogaming : an introduction to archaeology in and of video games - Reinhard, Andrew (Berghahn Books, 2018)
Video games exemplify contemporary material objects, resources, and spaces that people use to define their culture. Video games also serve as archaeological sites in the traditional sense as a place, in which evidence of past activity is preserved and has been, or may be, investigated using the discipline of archaeology, and which represents a part of the archaeological record. This book serves as a general introduction to "archaeogaming"; it describes the intersection of archaeology and video games and applies archaeological method and theory into understanding game-spaces as both site and artifact.